Three-phase ac-dc power supply design and experiments using a sic based power module - Raval, Chintan A. (Kansas State University, 2017)
The rise of Wide Band Gap (WBG) devices has brought excitement in the field of Power converters. The WBG based converter can operate at the very high frequency and temperature making them ideal to use in harsh environments. The commercialization of WBG devices such as SiC and GaN MOSFETs has made it interesting for power engineering professionals all over the world. The use of WBG devices capable of operating at high switching frequencies reduces the overall system size dramatically with added benefit of improved power quality at high temperature. The main goal of this thesis is to design and test an AC-DC converter based on a SiC power module. The designed rectifier can be considered an active rectifier equipped with a controller to constantly provide feedback for modification of switching signals to get the desired output voltage. The designed active rectifier converts the varying frequency input power supply into rectified DC voltage while keeping the power factor of the system to unity. This thesis covers elementary information on power supply design, switching schemes and design of the controller. System arrangement will provide more light on the use of Six Channel MOSFET Gate Driver from CREE with the overall experimental setup. The experimental analysis will summarize the behavior of the system where information on achieved rectification, effect on the line currents at the generator and concluding power factor representation is described.
Keywords: Wide Band Gap; Active rectifier; Unity Power Factor